IMPLEMENTASI PERMENDIKNAS NO 15 TAHUN 2010 TENTANG STANDAR PELAYANAN MINIMAL PENDIDIKAN DASAR DI KECAMATAN PEMAHAN KABUPATEN KETAPANG - Ihwan E.01109001, Miftahul (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The writing of this research is aimed to give a definition aboutMinimum Standard of Basic Education which must be applied by Institutiot of education Ketapang regency to increase the education service in ketapang regency. The problem in this research is the condition of the teacher resource is not only less in quantity but also in quality teachersquality. And the condition of the infrastructure is still not good enough.  Results from this research is indicate that the process implementation of Minimum Standard of Basic Education in  pemahan  sub regency is not  less than the maximum. The essential cause of  not maximal  this implementation process is low  attention of officers to directly involve in the field and just rely on the UPPK officers who are less in the number of employees that causing the employees less sensitive of actual needs which perceived by the schools. Thus, in giving aid educators and infrastructure is uneven. Beside that, in the process of implementation, inexistence of standard operating procedures (SOP) than became an obstacle as well as the recruitment of teachers by the government is not in accordance with the needs on the field. Tofollowing the phenomena, officer  Institution of education in Ketapang regency must do anobservation on the field directly to find out the needs that should take precedence in improving educational services. Adding UPPK officers in a sub regency and recruit  a competent educators according to the needs of existing schools in the field. Keyword : Minimum Standart Service of Education, Basic Education, Quality of education.